Scientific Opinion related to a notification from DuPont Nutrition Biosciences Aps on behenic acid from mustard seeds to be used in the manufacturing of certain emulsifiers pursuant to Article 21(2) of Regulation (EU) No 1169/2011 – for permanent exemption from labelling - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA); Dominique Turck; Jean‐Louis Bresson; Barbara Burlingame; Susan Fairweather‐Tait; Marina Heinonen; Karen Ildico Hirsch‐Ernst; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Monika Neuhäuser‐Berthold; Grażyna Nowicka; et al. (EFSA Journal, 2016)
Abstract Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion related to a notification from DuPont Nutrition Biosciences Aps on behenic acid from mustard seeds to be used in the manufacturing of certain emulsifiers pursuant to Article 21(2) of Regulation (EU) No 1169/2011 – for permanent exemption from labelling. Behenic acid is produced from rapeseed–mustard seed variants prevalent in India, namely Brassica juncea (L.) Czern. (oriental mustard), Brassica rapa (L.) (brown/yellow Sarson or Toria), Brassica napus (L.) (rapeseed) and Brassica nigra (L.) W.D.J.Koch (black mustard). No human or animal allergenicity data were provided by the applicant for either behenic acid or the emulsifiers manufactured from behenic acid. Based on enzyme‐linked immunosorbent assay (ELISA) data, the Panel considers that proteins and peptides may not be carried over into behenic acid after the two distillation steps reported in the manufacturing process in amounts beyond 1 mg/kg. The Panel notes that the maximum amount of mustard protein that could be consumed from emulsifiers manufactured from behenic acid (E 470a, E 471 and E 477) on a single occasion by an adult under the proposed conditions of use would be around 0.00119 mg, which is about 1,000 times lower than the protein doses reported to trigger allergic reactions in mustard‐allergic individuals (around 1 mg). On the basis of the data presented, the Panel concludes that oral consumption of emulsifiers manufactured using behenic acid from mustard seeds (E 470a, E 471 and E 477) are unlikely to trigger an allergic reaction in susceptible individuals (i.e. mustard‐allergic individuals) under the proposed conditions of use.